Pengaruh Biochar terhadap Pertumbuhan Padi dalam Sistem Aerobik - Suli Suswana (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2019)
An application of biochar to the intensive weathered soils potentially can change physical and chemical properties of the soils, improved soil function and increased yield of crops. A meta-analyses evaluation showed a significant correlation between biochar and plants productivity, that means there are benefits of biochar application to the soils on plants productivities, that was increased 10%.This experiment was used Randomized Completed Block Design with 8 treatments and 3 replications. The treatments are: contr), 20 ton biochar ha-1, 40 ton biochar ha-1, 50 ton biochar ha-1, 60 ton biochar ha-1, 10 ton biochar + 10 ton poultry litter ha-1, 20 ton biochar + 20 ton poultry litter ha-1, 30 ton biochar + 30 ton poultry litter ha-1. The results showed biochar 20 ton ha-1 could increase significantly of plant heigh, number of punicles per clump, and the weight dried straw per clump. Whereas, application combination 20-30 ton biochar ha-1 + 20-30 ton poultry litter ha-1 could increase amount of tillers per clump, amound of punicles per clump, and weight dried straw (total biomass) per clump significantly.